Development of an iron-based alloy with a high degree of shape recovery - Mohammed, Ahmed Sundus; Akimov, Oleg; Kostyk, Kateryna (Eastern-European Journal of Enterprise Technologies, 2017)
We examined a technological process for receiving an iron-based alloy with a shape memory effect, substantiated the choice of chemical composition of the alloy, and selected thermal treatment modes. Research results into scale resistance revealed at heating the samples in the temperature range of 600–1000 °C, surface oxidation was not observed. In the course of experiment on corrosion resistance of the alloy, we found that the alloy is corrosion resistant and is not inclined to change the weight when exposed to 10 % solution of sulfuric acid. Study into the microstructure confirmed the existence of dispersion hardening in the alloy after the aging regimes. Diffractogram of the alloy after hardening at a temperature of 1150 °C and cooling in the open air showed a surge that corresponds to γ-Fe, therefore, the content of residual austenite in the alloy is 100 %. Research results demonstrated that the degree of shape recovery of the proposed alloy is 78–97 %. The proposed alloy is plastic enough; it may undergo hot, warm and cold deformation in the open air. We constructed mathematical models of the impact of chemical composition of the alloy on tensile strength of the alloy and the values of a shape memory effect. The iron-based alloy with a shape memory effect can be obtained both under laboratory conditions and on industrial equipment.